PENGARUH LAJU ALIRAN TERHADAP PENURUNAN CEMARAN INSTALASI PENGOLAHAN AIR LIMBAH DOMESTIK DENGAN SISTEM BIOFILTER - Sarasdewi, Ayu Putu; Semadi Antara, Nyoman; Suryawan Wiranatha, A.A.P.Agung (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 3 No 2 (2015): Juni)
The aim of this study was to reduce ammonia contamination, Chemical Oxygen Demand (COD), Biological Oxygen Demand (BOD), and Total Suspended Solid (TSS) in the waste water effluent of IPAL using biofilter system. The biofilter system was made of glass tubs containing filter media such as gravel, sand, and zeolite withthickness of 30 cm each. Among filter media was laid by fibers with a thickness of 5 cm. This laboratory scale biofilter system was used to conduct experiment which was design by using a simple randomized block design (RBD). The treatment experimented was the flow rate of wastewater which was consist of four levels, namely 50, 100, 150, 200 ml/min. The results showed that wastewater flow rate variation significantly affected decreasing levels of organic contaminants.The slower rate of wastewater flow haved the faster of time needed to reach steady state conditing. The optimum flow rate to reduce level of organic contaminants of domestic wastewater was 50ml/min. The effectiveness of decreasing the ammonia, COD, BOD, and TSS 91.42%, 74.77%, 52.95%, and 72.76%.
Keywords: 39,